Self-oscillating floating of a spherical liquid crystal elastomer balloon under steady illumination. (1st March 2023) - Cheng, Quanbao; Cheng, Wenyan; Dai, Yuntong; Li, Kai
Highlights: A new self-floating balloon composed of optically-responsive liquid crystal elastomer(LCE) is established. The LCE balloon has two typical motion regimes, namely the divergence regime and self-floating regime. The critical conditions for triggering the self-floating are analytically derived. The amplitude and frequency of self-floating can be designed by several parameters. Abstract: Self-oscillations have the advantages of direct energy harvest from the constant environment, autonomy, and portability of the equipment, and it is desired to develop a wealth of new self-excited motion modes for greatly expanding the application of active machines. In this paper, a self-oscillating floating balloon is creatively constructed, which consists of an optically-responsive liquid crystal elastomer (LCE) spherical balloon under steady layered illumination. A theoretical model is developed based on the well-established dynamic LCE model and the ideal gas model, and dynamics of the self-floating balloon is calculated numerically. The results show that the LCE balloon can self-float continuously up and down by the steady layered illumination, which is elucidated to arise from the coupling between the process-related buoyancy and the constant gravity. The self-floating of the LCE balloon can be maintained by the energy of the constant illumination, which compensates for the damping dissipation of the system. Furthermore, the effects of the system parameters on the triggering condition, amplitude and equilibrium position of the self-floating are extensively investigated. The self-floating balloon constructed in this paper will expand the application scope of self-oscillations, and its simple operation and accurate control will enjoy great application prospects in the fields of soft robotics, targeted therapy, military monitoring and environmental measurement. Graphical abstract: Image, graphical abstract